Targeting smooth muscle cell phenotypic switching in vascular disease - Chakraborty, Raja; Chatterjee, Payel; Dave, Jui M.; Ostriker, Allison C.; Greif, Daniel M.; Rzucidlo, Eva M.; Martin, Kathleen A. (JVS-vascular science, 2021)
The phenotypic plasticity of vascular smooth muscle cells (VSMCs) is central to vessel growth and remodeling, but also contributes to cardiovascular pathologies. New technologies including fate mapping, single cell transcriptomics, and genetic and pharmacologic inhibitors have provided fundamental new insights into the biology of VSMC. The goal of this review is to summarize the mechanisms underlying VSMC phenotypic modulation and how these might be targeted for therapeutic benefit. We summarize findings from extensive literature searches to highlight recent discoveries in the mechanisms underlying VSMC phenotypic switching with particular relevance to intimal hyperplasia. PubMed was searched for publications between January 2001 and December 2020. Search terms included VSMCs, restenosis, intimal hyperplasia, phenotypic switching or modulation, and drug-eluting stents. We sought to highlight druggable pathways as well as recent landmark studies in phenotypic modulation. Lineage tracing methods have determined that a small number of mature VSMCs dedifferentiate to give rise to oligoclonal lesions in intimal hyperplasia and atherosclerosis. In atherosclerosis and aneurysm, single cell transcriptomics reveal a striking diversity of phenotypes that can arise from these VSMCs. Mechanistic studies continue to identify new pathways that influence VSMC phenotypic plasticity. We review the mechanisms by which the current drug-eluting stent agents prevent restenosis and note remaining challenges in peripheral and diabetic revascularization for which new approaches would be beneficial. We summarize findings on new epigenetic (DNA methylation/TET methylcytosine dioxygenase 2, histone deacetylation, bromodomain proteins), transcriptional (Hippo/Yes-associated protein, peroxisome proliferator-activity receptor-gamma, Notch), and β3-integrin-mediated mechanisms that influence VSMC phenotypic modulation. Pharmacologic and genetic targeting of these pathways with agents including ascorbic acid, histone deacetylase or bromodomain inhibitors, thiazolidinediones, and integrin inhibitors suggests potential therapeutic value in the setting of intimal hyperplasia. Understanding the molecular mechanisms that underlie the remarkable plasticity of VSMCs may lead to novel approaches to treat and prevent cardiovascular disease and restenosis.